2007
DOI: 10.1002/lt.21183
|View full text |Cite
|
Sign up to set email alerts
|

Effect of body mass index on the survival benefit of liver transplantation

Abstract: Obese patients are at higher risk for morbidity and mortality after liver transplantation (LT) than nonobese recipients. However, there are no reports assessing the survival benefit of LT according to recipient body mass index (BMI). A retrospective cohort of liver transplant candidates who were initially wait-listed between September 2001 and December 2004 was identified in the Scientific Registry of Transplant Recipients database. Adjusted Cox regression models were fitted to assess the association between B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
107
3
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(121 citation statements)
references
References 18 publications
7
107
3
4
Order By: Relevance
“…6 The study reported in this issue of Liver Transplantation by Pelletier et al 7 shows that the prevalence of obesity has increased significantly in more recent years. Of those who underwent transplantation between 2001 and 2004, 32.5% were obese, and among them, 8.4% were severely obese and 3.2% were morbidly obese.…”
Section: See Article On Page 1678mentioning
confidence: 98%
See 2 more Smart Citations
“…6 The study reported in this issue of Liver Transplantation by Pelletier et al 7 shows that the prevalence of obesity has increased significantly in more recent years. Of those who underwent transplantation between 2001 and 2004, 32.5% were obese, and among them, 8.4% were severely obese and 3.2% were morbidly obese.…”
Section: See Article On Page 1678mentioning
confidence: 98%
“…In both renal and liver transplant recipients, cardiovascular complications were the main cause of increased mortality. 6,9 Pelletier et al 7 examine survival benefits of liver transplantation according to recipient BMI. Using the Scientific Registry of Transplant Recipients database from September 2001 to December 2004, the authors report that transplant recipients, when compared to those who were listed and did not undergo transplantation, had survival benefits irrespective of their BMI.…”
Section: See Article On Page 1678mentioning
confidence: 99%
See 1 more Smart Citation
“…IMPLICATIONS OF OVERWEIGHT IMPLICATIONS OF OVERWEIGHT IMPLICATIONS OF OVERWEIGHT IMPLICATIONS OF OVERWEIGHT IMPLICATIONS OF OVERWEIGHT AND OBESITY IN LIVER AND OBESITY IN LIVER AND OBESITY IN LIVER AND OBESITY IN LIVER AND OBESITY IN LIVER TRANSPLANTATION TRANSPLANTATION TRANSPLANTATION TRANSPLANTATION TRANSPLANTATION There are several implications of obesity in patients undergoing liver transplantation. Studies have shown that the obesity of donor and recipient may influence operative results [36][37][38][39][40][41][42] . Pre-obese patients are more likely, to develop primary graft dysfunction, delayed graft function after the operation and have increased risk of death 36,37 .…”
Section: Introduction Introduction Introduction Introduction Introducmentioning
confidence: 99%
“…Studies have shown that the obesity of donor and recipient may influence operative results [36][37][38][39][40][41][42] . Pre-obese patients are more likely, to develop primary graft dysfunction, delayed graft function after the operation and have increased risk of death 36,37 . These findings have not been universal, however, 38 .…”
Section: Introduction Introduction Introduction Introduction Introducmentioning
confidence: 99%